ARE EUROPEAN VOTERS MOTIVATED? THE CASE OF THE EUROPEAN PARLIAMENT ELECTIONS IN THE REPUBLIC OF SLOVENIA IN 2024 - Matić, Petar; Mijatović, Marko (Political Review, 2024)
The elections for the European Parliament in the Republic of Slovenia on June 9, 2024 are part of a broader electoral process in which nine Slovenian deputies are elected to the European Parliament for the next mandate period 2024-2029. years. The aim of this paper is to describe and explain in basic terms the overall Slovenian and European context of the elections, the special characteristics of the Slovenian political scene, and the results of these elections. On this occasion, the traditional ideological division of Slovenian society on the right-center-left line came to the fore in the middle of the mandate of the left-center government of Robert Golob in the electoral system that favors large national parties (proportional system with one electoral unit without census, preferential voting), traditionally low turnout in European elections in Slovenia. Consultative referendums held in parallel on changing the electoral system (introduction of preferential voting), on laws on the cultivation and processing of hemp for medical purposes, laws that allow the use of marijuana and medical euthanasia also reflected some of the Government's priorities, the right-wing opposition's response, and finally the citizens' decisions.
Keywords: European elections; Slovenia; political parties; referendums; electoral system; contextual political analysis